A CONTRASTIVE ANALYSIS OF SENTENCE STRUCTURE IN UZBEK, RUSSIAN, AND ENGLISH - Abduvakhobova Dilnoza Jorabekovna; Ashurov Alisher (TADQIQOTLAR, 2025)
Annotation:  This  article  analyzes  the  structural  differences  in  sentence construction among Uzbek, Russian, and English. It discusses the syntactic roles of sentence constituents, the order of elements, morphological markers, tense and aspect systems, and pragmatic nuances such as emphasis and intonation. The analysis is based on contrastive linguistic methods and explores how these languages utilize grammar and structure to express meaning. This comparative study aims to support theoretical linguistics  and  second  language  acquisition,  especially  for  learners  and  educators working across these three linguistic systems.